De novo dedifferentiated SDH-deficient gastrointestinal stromal tumor with MDM2 amplification: case report and literature review - Gong, Qi-Xing; Ding, Ying; Zhang, Wei-Ming; Zhang, Jia-Wen; Zhang, Zhi-Hong (Frontiers in Oncology, 2023)
The dedifferentiation of the gastrointestinal stromal tumors (GISTs) has been reported in a small number of cases, usually under the pressure of the tyrosine kinase inhibitor (TKI) treatment. Herein, we described a de novo dedifferentiated GIST with the SDH deficiency in a 32-year-old Chinese woman. The tumor was located on the lesser curvature of the gastric antrum, measuring 4.1x9.1 cm2. Microscopically, the tumor was composed of 2 distinct morphological populations, mild epithelioid cells arranged in the multinodular growth pattern and hyperchromatic spindle cells arranged in the fascicular or sheet-like architecture. The two zones showed different immunophenotypes. The former proved to be an epithelioid GIST with the positive expression for C-KIT, DOG-1, and CD34, and the latter expressed the CKpan and P53, but negative for the C-KIT, DOG-1, and CD34. However, the SDHB staining was negative in both areas. Genetically, the next-generation sequencing (NGS) analysis showed the SDHC mutation (p.S48*) in both components and the MDM2 amplification was only in the spindle cell area. The lesion was diagnosed as the SDH-deficient GIST with the epithelial cell dedifferentiation. We proposed that the P53 associated gene alteration or other alternative escape mechanisms for the KIT-independent signaling pathways might play a role in the dedifferentiation.